Task force: connecting India, China and Southeast Asia ; new socio-economic developments - Senz, Anja-Désirée; Reinhardt, Dieter (Duisburger Arbeitspapiere Ostasienwissenschaften, 2014)
The border regions between Northeast India, Bangladesh, Myanmar and Southwest China are characterized by close historical, intra-ethnic relations and a developing civil society sector as well as violent conflicts and disputes about hydropower and resource extraction projects. What is more, this region will be affected by climate change. The articles reflect expanding regional economic relations, resource extraction projects, climate change challenges, minority issues and the potential for further involvement of the civil society.
Zsfassung in dt. und engl. Sprache
Keywords: Arbeitspapier; Graue Literatur